Development of industrial exports: papers presented at the training course organized by UNIDO and the UNCTAD/GATT International Trade Centre in co-operation with the Government of the Socialist Federal Republic of Yugoslavia - United Nations Industrial Development Organization; International Trade Centre UNCTAD/GATT.; Yugoslavia (New York, United Nations, 1970)
The papers published in this volume are based on selected lectures presented to a training course. The papers reflect the diverse approaches and viewpoints of experts and not necessarily the views of the secretariat of UNIDO or the UNCTAD / GATT International Trade Centre
"United Nations publication. Sales no.: E.70.II.B.26."
Includes bibliographies.
osc 12/12/2018
Loans
Keywords: Export marketing; Exports; Developing countries